Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Kebijakan Dividen: Studi Kasus Perusahaan Manufaktur di Indonesia - Akal, Andi Tenri Uleng; Nurlaela, Nurlaela; Nur, Sri Wahyuni (JURNAL MANAJEMEN BISNIS, 2021)
Profitability (ROA) and leverage (DER) have a favorable and material impact on the dividend policies of food and beverage manufacturing companies listed on the IDX. That is, if profitability and leverage continue to improve, so will the dividend policy. In comparison to liquidity (current ratio), which has a positive but negligible effect on the dividend policy of food and beverage manufacturing companies that are listed on the IDX. It may be concluded that while liquidity owned by the company can help enhance dividends, it cannot have a major impact on dividend policy reform. Increased dividend policy will entice investors. Thus, dividend policy can be improved by this research by optimizing asset utilization (ROA) and lowering the danger of debt relief (DER).